1991
DOI: 10.1161/01.cir.83.2.559
|View full text |Cite
|
Sign up to set email alerts
|

Relation between leisure-time physical activity and blood pressure in older women.

Abstract: Although there is some evidence that physical activity may decrease blood pressure in young and middle-aged women, the physical activity-blood pressure association in older women has rarely been studied. Although physical activity was associated with lower fasting and 2-hour postchallenge insulin levels (p<0.01 for trend), adjustment for insulin levels did not alter blood pressure differences among activity groups. We conclude that habitual physical activity in older women is associated with clinically importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 11 publications
5
51
1
6
Order By: Relevance
“…36 Several population studies have demonstrated an inverse relationship between leisure time physical activity and BP levels. [37][38][39] The present survey indicated no relationships between both occupational and leisure time physical activity and BP levels. Commuting physical activity was inversely associated with BP levels in men and is very important to urban Chinese.…”
Section: Journal Of Human Hypertensioncontrasting
confidence: 68%
“…36 Several population studies have demonstrated an inverse relationship between leisure time physical activity and BP levels. [37][38][39] The present survey indicated no relationships between both occupational and leisure time physical activity and BP levels. Commuting physical activity was inversely associated with BP levels in men and is very important to urban Chinese.…”
Section: Journal Of Human Hypertensioncontrasting
confidence: 68%
“…Therefore, individuals living in neighborhoods with high street connectivity are more likely to meet recommended levels of walking. In addition, it has been suggested that walking "physical activity" of light-to-moderate intensity may be a particularly effective method of lowering blood pressure in older adults [35]. Perceived quality aesthetics in our study was associated with lowering hypertension.…”
Section: Discussionsupporting
confidence: 49%
“…Regular, dynamic, aerobic physical activity is associated with a reduced risk of hypertension 1,2 A significant inverse relationship between regular physical activity and blood pressure (BP) has been reported, 3 although some data did not confirm favourable effects of exercise in essential hypertension. 4,5 In recent years, there has been considerable interest in circulatory after-effects of single physical exercise.…”
Section: Introductionmentioning
confidence: 99%